Facile fabrication of freestanding graphene nanoplatelets composite electrodes for multi battery storage - Chong, Woon Gie; Ng, Zen Ian; Yap, Shek Li; Foo, Chuan Yi; Jiang, Heng; Guo, Hang; Lim, Hong Ngee; Huang, Nay Ming (Elsevier, 2022)
Graphene electrode offers an exceptional high energy storage capacity in various electrochemical systems, but the practical applications of graphene electrodes in ion storage devices are hindered by high processing cost for a high crystallinity graphene. Thanks to the redox-amphoteric attributes of graphene, acceptor-type graphite intercalated compound (GICs) are receiving great interest for novel battery systems. Herein, freestanding, highly conductive, porous graphene nanoplates film (GNPF) are prepared by a facile, one step phase inversion approach. The GNPF electrodes present an excellent electrochemical performance in aluminium ion battery (AIB) with a high areal loading of 4.14 mg cm−2 delivers a remarkable specific capacity of 83 mAh g −1 (translated to 0.35 mA cm−2) at 1 A g −1 after 2000 cycles. The porous GNPF electrodes endows high voltage storage in a dual carbon battery (DCB) system. The battery presents superior cycling stability at high cut-off voltage of 5.0 V with a reversible capacity of 50 mAh g−1 after 100 cycles at 50 mA g−1. The current approach simplifies the fabrication of freestanding graphene-based electrodes while maintaining the electrochemical activity and structural stability of GNPs for high electrochemical energy storage applications.